Imaging Lymphoma With F-18 Fluorodeoxyglucose PET-CT: What Should Be Known About Normal Variants, Pitfalls, and Artifacts? - Vangu, Mboyo Di Tamba; Momodu, Jaleelat I. (Frontiers in Nuclear Medicine, 2022)
18F fluorodeoxyglucose ([F-18] FDG) PET-CT has gained popularity in the management of many types of malignancies. Today, imaging patients with lymphoma using of [F-18] FDG PET-CT not only is considered as a state-of-the-art tool but also has taken a central place for therapeutic decisions. In fact, accurate staging at diagnosis is imperative to prevent under treatment of individuals with advanced disease. In Hodgkin's lymphoma, in particular, the current role of interim [F-18] FDG PET imaging goes beyond speculations in the adaptation of different therapeutic strategies. Therefore, the use of such a critical imaging modality should go hand in hand with sound interpretation that provides accurate results. As the number patients referred for PET-CT continues to increase, imaging specialists should remain aware of the inherent limitations linked to the integrated imaging system that may introduce potential pitfalls related to the machine or the administered [F-18] FDG. Knowledge of the normal physiologic biodistribution of [F-18] FDG, its physiologic variants, and of all the potential pitfalls and artifacts is paramount to avoid misinterpretation. Recognition of the limitations of [F-18] FDG PET-CT will increase the confidence of practicing clinicians on the modality and impact positively on the management of patients. In this article, we will review the normal physiological variants, technical artifacts, and diagnostic pitfalls in lymphoma. Highlighting the limitations of [F-18] FDG PET-CT imaging should warn interpreting specialists to find measures that mitigate them and improve reporting results.